BASIC CONCEPTS OF CAREER COUNSELING IN THE WORLD OF EDUCATION IN HIGH SCHOOLS AND VOCATIONAL HIGH SCHOOLS - Restu Fauziah; Daharnis; Mega Iswari (Yayasan Citra Dharma Cindekia, 2022)
In this article discusses about career counseling in high school and vocational education units, career decision making is an important problem experienced in human life from childhood to adulthood including adolescence. This period is considered a very important period in a person's life, especially the exploration phase. In the implementation of education in SMA and SMK, guidance and counseling teachers or counselors play a role in helping the achievement of personal, social, learning, and career development of students/counselors. At this level, the guidance and counseling teacher or counselor carries out all the functions of guidance and counseling, namely the functions of understanding, facilitation, adjustment, distribution, adaptation, prevention, improvement, advocacy, development, and maintenance. Therefore, it is very important the role of a counselor in helping students in educational units, especially in high school and vocational schools, to develop and choose their careers in the future. Counselors can use a variety of services and approaches in developing and selecting students' careers.